Infant feeding practices in rural Bangladesh - Gazi, Rukhsana; Karim, Fazlul; Ali, Ahmed (BRAC Research and Evaluation Division (RED), 2020)
This study was part of a longitudinal study on the consequences of low birth weight (LBW) babies which was carried out in three unions of Manikganj district during 1993- 1994. This study aimed to assess the breastfeeding practices among infants and to compare the weaning practices among LBW and normal birth weight infants. A total of 644 infants were registered within 48 hours of birth and they received monthly follow-up visit upto one year of age. Although breastfeeding was universal in the study population, detrimental feeding practices, such as the administration of pre-lacteal foods (75%) and rejection of colostrum (1 1 %) were prevalent among the mothers. There was a delay in initiation of first breastfeeding. Although 77% of the mothers exclusively breastfed their babies at the first month, the prevalence of exclusive breastfeeding decreased to 50% by the third month. The main reason for giving additional foods was that the mothers felt breastmilk was insufficient. A significantly higher proportion of LBW infants received additional feeding than the normal infants. It might be due to the mothers perception that the additional foe<i to thin looking LBW babies was needed for their quick recovery and proper growth. Health workers should receive practical training on breastfeeding counselling. Weekly follow-up and monitoring of breastfeeding practices for at least one month can be introduced in the breastfeeding interventions. Audio-visual aids can be used to teach mothers how to breastfeed effectively. LBW babies require more frequent and short feedings. Expressed breast milk can be fed to LBW babies who can not suck.